Electrical Acupuncture Efficacy on Inflammatory Pain - Minghong SUI; Jingjing LI; Yun XIANG; Guojian SHU; Dongmei JIN; Tiebin YAN (康复学报)
Objective:To explore electrical acupuncture (EA) therapy effects on complete freund's adjuvant (CFA) induced inflammatory pain model rats.Methods:A total of 30 SD male rats were randomly divided into normal saline+Sham Electroacupuncture (NS+SE) group, CFA+Sham EA (CFA+SE) group and CFA+Electroacupuncture (CFA+EA) group, with 10 rats in each group. Mechanical and thermal allodynia were assessed before and after EA treatment at Day 4 after CFA injection. Dialysate of the rats was collected from the right tibialis anterior muscle by microdialysis at Day 5 from 1.5 hours before the treatment until 1.5 hours after treatment. Adenosine concentration in the dialysate was analyzed by HPLC.Results:At Day 4 after injection of paclitaxel, EA treatment can obviously increase the pain threshold of CFA-induced inflammatory pain rat model. The mechanical allodynia showed that the VonFrey result of the CFA+EA group was significantly decreased (P<0.05) after treatment, and the PWL results also significantly prolonged (P<0.05) compared with the NS+SE group and the CFA+SE group.Conclusion:EA can increase rats pain threshold of CFA-induced inflammatory pain, and alleviate inflammatory pain. The alleviate of inflammatory pain might through adenosine increasment in the local tissue fluid around the acupoints.